New datings of deposits from Odra river valley - stratigraphic consequences and interpretation at fluvial succession - Gontaszewska-Piekarz, Agnieszka; Szczepaniak, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents organic sediments age analysis in Odra river valley in Słubice, western Poland. In this middle reach of Odra valley reach the uppermost fluvial deposits contain several alternate layers of organic sediments. These deposits have been mostly interpreted as the Holocene fluvial (floodplain) sediments, even if visible admixture of organic matter is not observed. However, there is also another hypothesis.
Keywords: geotechnical studies; alluvial deposits; radiocarbon dating; Holocene; Słubice; Odra river valley; badania geotechniczne; złoża aluwialne; datowanie radiowęglowe; holocen; Dolina Odry